Zavest dijakov o jezikovni zvrstnosti in vlogah knjižnega jezika - Vogel, Jerca (Slavia Centralis, 2020)
Students’ Awareness of the Language Varieties and the Functions of the Standard Language Discussing the identity function of language as well as different language varieties in teaching Slovenian as first language has only changed slightly in the last two decades. Therefore, based on the linguistic discussions on the differences between prevailing language stratification theory and communicative practise, three main issues have been investigated, namely how do students understand the concept of standard language, what is their experience with using the standard language and finally, in which speaking situations is the use of a standard language necessary.